Clinical characteristics, mortality and pain tolerance in stable versus acute presentation of coronary heart disease - Fladseth, Kristina (UiT The Arctic University of Norway, 2022)
Despite immense progress in the prevention, diagnosis and treatment of coronary heart disease, several challenges remain. In more than half of patients referred to coronary angiography for stable and unstable angina, no obstructive coronary artery disease (CAD) is found. At the same time, some patients present for the first time with already extensive CAD. Further, the management of unstable angina patients after implementing high-sensitivity troponins is uncertain. We investigated if we could improve the selection of unstable angina patients to coronary angiography, the outcomes of unstable angina compared to stable angina and myocardial infarction (MI), and how pain tolerance affects when and how CAD presents. We applied data from patient hospital records, the local and national coronary angiography registry and the Tromsø Study. Pain tolerance was assessed using a cold pressor test in the Tromsø Study. Paper I is a retrospective cohort study, while papers II and III are prospective cohorts studies. We used logistic regression and Cox proportional hazard regression analyses. In paper I, adding symptom characteristics to cardiovascular risk factors, we created a risk score to predict obstructive CAD in unstable angina patients. This score performed better than guidelines and other risk scores. In paper II, we found that unstable angina patients had a similar risk of cardiovascular events but a higher risk of death than stable angina patients. Unstable angina had a lower 1-year risk of cardiovascular events and death than non-ST segment elevation MI. In paper III, individuals with low pain tolerance had a higher risk of coronary angiography, obstructive CAD and death. Pain tolerance was not associated with the clinical presentation or extent of CAD. Our findings confirm that unstable angina patients have a better prognosis than MI patients and support the newest guidelines recommending fewer invasive coronary angiographies in unstable angina patients. The discrepancy in when and how CAD presents is still ...